Decoding the Role of Gender in the Relationship Between the Online Payment System and SME Performance: A Case Study Investigating an Emerging Economy—Bangladesh - Nahar, Sharmin (Frontiers in Research Metrics and Analytics, 2022)
This research examines the use of online payment systems and their impact on the performance of SMEs in an emerging economy, using the Technology Acceptance Model (TAM) and Resource-Based View (RBV). The use of online payment systems has a considerable positive effect on SMEs’ performance, according to data obtained from 302 SMEs in Bangladesh through face-to-face surveys. Male SME owners (entrepreneurs) are more likely to focus on perceived usefulness, whereas female SME entrepreneurs are more likely to focus on perceived ease of use. The study’s findings will add to the scarce research on the impact of using online payment systems on business performance in the context of SMEs in emerging economies, in addition to enhancing the online payment system adoption literature.